A MODEL FOR INTEGRATING FORMAL AND NON-FORMAL EDUCATION IN INDONESIA: A CASE STUDY OF CROSS-SECTOR AND THIRD-PARTY SUPPLY CHAIN MANAGEMENT - Rahman, Moh. Rifqi; Fuad, Ah. Zakki; Zuhri, Achmad Muhibin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
This research expands upon existing theories proposed by Zaniyati and Fathurrohman concerning educational policy integration models, examining the challenge of educational institutional dualism arising from the enactment of Law Number 20 of 2003 in Indonesia. Despite this challenge, the emergence of regional regulations aimed at integrating Islamic non-formal educational institutions (diniyah takmiliyah) with formal educational institutions presents a unique opportunity for study. This research investigates and refines the integration model between diniyah takmiliyah and formal education, specifically within the East Java Province regions of Sumenep and Pasuruan. Then, utilizing a case study methodology embedded within a political research framework, this research draws upon institutional and actor-based approaches to analyze data collected through document analysis and in-depth interviews. Data analysis adheres to the rigorous methods proposed by Miles et al., encompassing data condensation, data display, and conclusion drawing stages. Findings reveal that the integration model between diniyah takmiliyah and formal educational institutions manifests as a synergistic single/cross-sector and third-party supply management model. This research contributes to the scholarly discourse by proposing the investigation of the effectiveness and a factorial analysis of these two integration models for future research endeavors. Abstrak: Penelitian ini mendalami dan mengembangkan dua teori yang dikemukakan oleh Zaniyati dan Fathurrohman mengenai model integrasi kebijakan pendidikan. Landasan penelitian ini adalah tantangan dualisme kelembagaan pendidikan yang muncul sebagai dampak dari diberlakukannya Undang-Undang Nomor 20 Tahun 2003. Meskipun demikian, tantangan dualisme ini mendorong lahirnya beberapa peraturan daerah yang berupaya mengintegrasikan lembaga pendidikan diniyah takmiliyah (pendidikan keislaman non-formal) dengan lembaga pendidikan umum (formal). Penelitian ini bertujuan untuk mengeksplorasi dan memperluas model integrasi antara pendidikan diniyah takmiliyah dengan pendidikan formal di Indonesia, dengan fokus pada dua wilayah di Provinsi Jawa Timur, yaitu Sumenep dan Pasuruan. Penelitian ini menggunakan pendekatan studi kasus dengan kerangka penelitian politik yang mengacu pada pendekatan kelembagaan dan aktor. Pengumpulan data dilakukan melalui telaah dokumen dan wawancara mendalam. Analisis data mengacu pada metode yang diusulkan oleh Miles dkk., meliputi tahapan kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa model integrasi antara lembaga pendidikan diniyah takmiliyah dengan lembaga pendidikan formal mengadopsi bentuk model integrasi sinergi single/cross-sector dan third-party supply management. Penelitian ini juga merekomendasikan pengujian efektivitas dan analisis faktorial terhadap kedua model integrasi tersebut untuk penelitian lebih lanjut.